Organisasi Kurikulum Dalam pendidikan Agama Islam - Muhammad Hafid Hafid; Mirawati; Zamsiswaya (STKIP Subang, 2025)
This study discusses the organization of curriculum in Islamic Education (PAI), which plays a central role in directing the learning process toward achieving the goals of Islamic education developing students who are faithful, knowledgeable, and possess noble character. The PAI curriculum is viewed as an integrated system that encompasses objectives, content, learning strategies, and evaluation, all grounded in Islamic values. Using a library research approach, this study examines the fundamental principles of curriculum development, including tawhid (unity of God), balance, integration, relevance, and continuity. It also explores various curriculum organization models such as the Separated Subject, Correlated, Integrated, the findings reveal that each model has distinctive strengths and characteristics in implementing Islamic values within educational institutions. In facing the challenges of globalization and the digital era, curriculum organization in Islamic education must be developed innovatively through improving teacher competence, integrating science and technology, and strengthening value-based evaluation systems. Therefore, a well-planned and flexible curriculum organization can create holistic, contextual, and relevant learning that meets the needs of modern society while remaining rooted in Islamic principles. Keywords: Curriculum, Islamic Education, Curriculum Organization, Development, Islamic Values Integration.